Recruiting young people to sensitive research: turning the ‘wheels within wheels’ - Turner, N.; Almack, K. (Taylor & Francis, 2016)
This article explores the difficulties encountered in recruiting participants for a study of young people living with a parent at the end of life. Far from being a smooth, linear process, recruitment was experienced as a series of overlapping challenges, characterised here as ‘wheels within wheels’. Where potential participants are constructed as vulnerable within the research process, access tends to be mediated by 'gatekeepers'. As such, gatekeepers are often positioned as 'people to get past' or even as adversaries. This article contributes to a growing literature that takes a more nuanced approach to exploring the complexities of relationships and negotiations with gatekeepers. We conclude with some reflections on the potential implications for young people in exigent sets of circumstances. If the routes 'in' to access young people are difficult, then this also raises questions about routes 'out' for young people and their access to support when living through challenging times.